HUBUNGAN POLA MAKAN DENGAN KEJADIAN OBESITAS PADA ANAK SEKOLAH DI SDIT ABATA SRENGSENG KEMBANGAN JAKARTA TAHUN 2020 - Oryza Intan Suri; Nurana Diana Mulyati (STIKes IMC Bintaro, 2022)
Introduction Research data of basic health points out the obesity prevalence which keeps growing in Indonesia. From 10,5 % (2007) to 14,8 % (2013), and then 21,8 % (2018). The purpose of this research is to enhance the knowledge of The relation between dietary habit and obesity cases toward students of SDIT ABATA Srengseng Kembangan Jakarta in 2020. Methodology of this research tends to be correlation descriptive using crosssectional approach. Student population of SDIT ABATA Srengseng Kembangan Jakarta is 436 children, the sample which is used is 108 respondents. The independent variable is dietary habit and the dependent variable is obesity cases. Research instruments using questionnaire through google foam. Data processing using SPSS with univariate and bivariate analysis. Data analysis using chi-squaretest and displayed in tables and narration form.The results of the research are 8-9 years old, male sex more than female, the majority of parental education is academy / college and the average parent's income is above the UMR / ≥ IDR 5 million. Based on the results of the Chi- Square test, it is found that there is a relation between dietary habit and obesity cases with a significant number or the p value is 0.000, this value is p <0.005 so that Ha is accepted, showing that there is a correlation between diet and obesity. The conclusion is that there is a relation between dietary habit and the incidence of obesity amid the elementary students of SDIT ABATA Srengseng Kembangan Jakarta in 2020. The suggestion is that respondents can adjust their dietary habit which includes types of food, frequency of food and food portions so that obesity does not occur in the future.